Against the mainstream: exceptional evolutionary stability of ZW sex chromosomes across the fish families Triportheidae and Gasteropelecidae (Teleostei: Characiformes) - Yano, Cassia Fernanda; Sember, Alexandr; Kretschmer, Rafael; Bertollo, Luiz Antônio Carlos; Ezaz, Tariq; Hatanaka, Terumi; Liehr, Thomas; Ráb, Petr; Al-Rikabi, Ahmed; Viana, Patrik Ferreira; Feldberg, Eliana; de Oliveira, Ezequiel Aguiar; et al. (Chromosome research, 2021)
Teleost fishes exhibit a breath-taking diversity of sex determination and differentiation mechanisms. They encompass at least nine sex chromosome systems with often low degree of differentiation, high rate of inter- and intra-specific variability, and frequent turnovers. Nevertheless, several mainly female heterogametic systems at an advanced stage of genetic differentiation and high evolutionary stability have been also found across teleosts, especially among Neotropical characiforms. In this study, we aim to characterize the ZZ/ZW sex chromosome system in representatives of the Triportheidae family (Triportheus auritus, Agoniates halecinus, and the basal-most species Lignobrycon myersi) and its sister clade Gasteropelecidae (Carnegiella strigata, Gasteropelecus levis, and Thoracocharax stellatus). We applied both conventional and molecular cytogenetic approaches including chromosomal mapping of 5S and 18S ribosomal DNA clusters, cross-species chromosome painting (Zoo-FISH) with sex chromosome-derived probes and comparative genomic hybridization (CGH). We identified the ZW sex chromosome system for the first time in A. halecinus and G. levis and also in C. strigata formerly reported to lack sex chromosomes. We also brought evidence for possible mechanisms underlying the sex chromosome differentiation, including inversions, repetitive DNA accumulation, and exchange of genetic material. Our Zoo-FISH experiments further strongly indicated that the ZW sex chromosomes of Triportheidae and Gasteropelecidae are homeologous, suggesting their origin before the split of these lineages (approx. 40-70 million years ago). Such extent of sex chromosome stability is almost exceptional in teleosts, and hence, these lineages afford a special opportunity to scrutinize unique evolutionary forces and pressures shaping sex chromosome evolution in fishes and vertebrates in general.
Keywords: molekulární evoluce; CGH; Humans; Sex Chromosomes; pohlavní chromozomy; Evolution, Molecular; Characiformes; Female; lidé; srovnávací genomová hybridizace; zvířata; sex chromosome evolution; malování chromozomů; Chromosome Painting; rDNA; chromosome rearrangements; ženské pohlaví; Chromosome Mapping; mapování chromozomů; Animals; Comparative Genomic Hybridization; Zoo-FISH